Vestibular dysfunction in pediatric patients with cochlear implantation: A systematic review and meta-analysis - Wu, Qiong; Zhang, Qin; Xiao, Qianwen; Zhang, Yuzhong; Chen, Zichen; Liu, Shuyun; Wang, Xueyan; Xu, Yong; Xu, Xin-Da; Lv, Jingrong; Jin, Yulian; Yang, Jun; et al. (Frontiers in Neurology, 2022)
Objective: Vestibular dysfunction may delay the achievement of balance and perception milestones in paediatric patients after cochlear implantation (CIM). Methods: A strategic literature search was done following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched the PubMed, Medline, Embase, Web of Science, and Cochrane Library databases from inception to July 2022. Studies involving the otoliths, semicircular canals, and balance function changes in children after CIM were included. Two reviewers independently assessed the level of evidence, methodological limitations, risk of bias, and characteristics of the cases. Matched pre- and postoperative vestibular functional test data, including ocular and cervical vestibular-evoked myogenic potential (oVEMP and cVEMP), caloric test, video head impulse test (vHIT), and Bruininks-Oseretsky Test 2 (BOT-2), were used to calculate the relative risk of vestibular disorders. Subgroup analyses were performed according to surgical approach, CIM device status and aetiology. Results: Twenty studies that met the inclusion criteria were selected for the meta-analysis. We observed significant vestibular dysfunction in paediatric patients with CIM. The results showed a statistically significant increase in abnormal cVEMP response (RR = 2.20, 95% CI = 1.87, 2.58, P < 0.0001), abnormal oVEMP response (RR = 2.10, 95% CI = 1.50, 2.94, P < 0.0001), and abnormal caloric test results (RR = 1.62, 95% CI = 1.20, 2.19, P = 0.0018) after implantation. Statistically significant differences were not found in the vHIT test results of all three semicircular canals before and after the operation (P > 0.05). Regarding static and dynamic balance, we found significantly poorer BOT-2 scores in children with CIM than in the normal group (mean difference = -7.26, 95% CI = -10.82, -3.70, P < 0.0001). Conclusions: The results showed that vestibular dysfunction may occur after CIM in paediatric patients. Some children experience difficulties in postural control and balance. Our results suggested that the comprehensive evaluation of vestibular function should be performed before and after CIM.